Glavkom in možnosti nevroprotektivnega zdravljenja - Zupan, Marija (Zdravniški vestnik, 2010)
Background: Glaucoma is a chronic progresssive optic neuropathy that often progresses despite lowering of intraocular pressure (IOP) to target levels. A need exists for therapies that prevent or limit the damage due to glaucoma, independent of therapies that simply lower IOP. The aim of neuroprotection in glaucoma is to slow down the progression by blocking the mechanisms that lead to apoptosis. Conclusions: The neuroprotective effect was demonstrated with brimonidine and betaxolol in clinical trial till now. Ginkgo biloba showed improvement of visual field damage in clinical studies on a small number of patients with NTG. Intravitreal application of Pralnacasan showed reduced ganglion cell apoptosis in an animal model with induced glaucoma. Vaccination with Glatiramer acetate has entered phase 2 trials for use in glaucoma patients.
Keywords: Drug Therapy; Dušikov oksid; Free Radicals; Glaucoma; Glavkom; Glutamates; Glutamati; Intraocular Pressure; Intraokularni pritisk; Nitric Oxide; Ocular Hypertension; oftalmologija; Oko, hipertenzija; preventiva; Prosti radikali; therapy; zdravljenje